ANALISA KOMPUTASI PARALEL MENGURUTKAN DATA DENGAN METODE RADIX DAN SELECTION - Favorisen R. Lumbanraja; Aristoteles Aristoteles; Nadila Rizqi Muttaqina (Jurnal Komputasi, 2020)
Increasing computing power is now achieved by replacing the programming paradigm with parallel programming. Parallel computing is a method of solving problems by dividing the computational load into small parts of the computation sub-process. This study describes the comparative analysis of parallel computations in the Selection Sort and Radix Sort algorithms. The data used are in the form of whole numbers and decimal numbers totaling 100 to 2 million data. The test was carried out with three scenarios, namely using two processors, four processors, and 3 computers connected to each other via a LAN network. The results showed that the parallel Selection Sort algorithm for small data was better than the parallel Radix Sort. On the other hand, parallel Radix Sort is better for millions of data than Selection Sort.